PENGARUH EKSPEKTASI PENDAPATAN TERHADAP MINAT BERWIRAUSAHA PADA MASYARAKAT (STUDI KASUS PADA DESA TUMPATAN NIBUNG DUSUN VI KECAMATAN BATANG KUIS KABUPATEN DELI SERDANG SUMATERA UTARA - Rizky Setiawan; Abdul Malik (Universitas Islam Sumatera Utara, 2021)
This study aims to determine the effect of income expectations on entrepreneurial interest in the people of Tumpatan Nibung Village VI Dusun VI, Batang Kuis District, Deli Serdang Regency. The sampling technique used was random sampling method, namely taking samples from the population at random without regard to the strata in the population of 94 people. Methods of data collection using a questionnaire. In the partial hypothesis test (t test) the income expectation variable has a positive and significant effect on the interest in entrepreneurship with a t count t table (9.969 1.661) and a significant value of 0.000 0.05. The results of the determination test obtained an R Square value of 0.519, meaning that the variable interest in entrepreneurship can be explained by 51.9% by the income expectation variable, while the remaining 48.1% is explained by other variables not included in this study.